Aplicación web para la gestión de la representatividad de árboles urbanos del proyecto de investigación Dinámica de crecimiento y servicios ecosistémicos del arbolado urbano de la ciudad de Loja - González Guamán, Johnny Fabián (2023)
Nowadays, the sustainable management of urban trees is a constant concern in various cities in the country, therefore many public institutions, formulate and implement policies destine to conservation, use and management of trees in urban areas. In this context, the forestry research project. "Growth dynamics and ecosystem services of urban grove in the city of Loja" seeks to elaborate and keep an inventory of trees within their respective limits, for this is required an application to manage the scientific and technical data collected by researchers manually, with the purpose of helping future research, giving rise to the research question: How could be help the researchers of the forestry project to obtain information related to records of trees in urban areas of the city of Loja? To solve this question, the Degree Project was developed with the ICONIX methodology, establishing the logical and physical architectural design models of the application represented in UML diagrams, based on the system requirements validated by the director of the forest project. Subsequently, these models were implemented applying the n-tier style, developing the backend and frontend under the JavaScript, React, Mapbox, Node, Express, Sequelize and MySQL technologies, obtaining a software product agreed by the researcher. Finally, various validation, black box and functional tests were carried out, to the director of the forest research project who functionally validated the entire application, and the tests of the API-REST services for future application integrations. Thus, the research question was reply, creating a web application that allows the user according to his role to manage the dasometric characteristics, morphological, ecological and ecosystem services of the grove of the city of Loja through interactive maps in the shortest possible time. Keywords: Urban forest management, ICONIX, Software, React, Node, MySQL.